Microgrids and Local Energy Systems - Jenkins, Nick (IntechOpen, 2021)
This book addresses important topical questions of microgrids and local energy systems. It begins with an investigation of the electrical protection of microgrids followed by a study of the power converters used and the utilization of multi-objective optimization for the selection of component ratings. Subsequent chapters address peer-to-peer energy trading in microgrids, local district heating and cooling systems, neighborhood generators used to supplement the utility electricity supplies in Iraq, and regulatory impediments to micro-wind generation in the United States.